Advances in computational methods in sciences and engineering 2005 : selected papers from the International Conference of Computational Methods in Sciences and Engineering (ICCMSE 2005) /: selected papers from the International Conference of Computational Methods in Sciences and Engineering (ICCMSE 2005). (2019) - Unknown
No abstract available